Exhibiting decolonising discourse: Critical settler education and 'the city before the city'. Issue 2 (2nd July 2016) - Johnson, Kay
Abstract: Canada, like other settler nations such as Australia, New Zealand, and the United States, faces considerable challenges in repairing and transforming relationships with Indigenous peoples. The country's reconciliation efforts need to overcome a general failure among non-Indigenous Canadians to acknowledge and understand colonialism and to recognise the contributions of Indigenous peoples. The education of the public thus becomes a key requirement for meaningful relationship building and social action. Cities are emerging as key sites for reconciliation, and their museums – as important spaces of adult education and public pedagogy – suggest possibilities for transforming Indigenous-settler relations. In this article, I use critical discourse analysis to examine how a collaborative exhibition with the Musqueam First Nation works pedagogically to provide opportunities for settler Canadians to critically question assumptions and to reimagine relations between Indigenous and settler societies. I identify three major discursive themes at the exhibition's Museum of Vancouver location, which I suggest have significant implications for critical settler education in the ways they interrogate, resist, and subvert dominant, colonialist discourse around city building and Indigenous peoples.